2001
DOI: 10.1379/1466-1268(2001)006<0394:aopaat>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma antibodies against the inducible Hsp70 with hypertension and harsh working conditions

Abstract: Autoantibodies against certain stress or heat shock proteins (Hsps) may play a role in the pathogenesis and/ or prognosis of some diseases. Using immunoblotting with human recombinant Hsps and univariate and multivariate logistic regression models, we have investigated the presence of antibodies against Hsp70, the inducible member of the 70-kDa family of heat shock proteins, and analyzed its possible association with hypertension and working conditions. Plasma and serum were collected from 764 steel mill worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 33 publications
0
42
0
1
Order By: Relevance
“…Although smoking (Newkirk et al 2012), hypercholesterolemia (Guisasola et al 2009), and microalbuminuria (Bianchi et al 2008) have been associated with increased circulating anti-Hsp70 levels and cases had greater prevalence/levels of these risk factors, the strength of the association was only slightly reduced by further adjustment for apoB, smoking, and AER. Previous studies have shown an association between circulating anti-Hsp70 antibody levels and single parameters of the MetS, such as hypertension, obesity, and dyslipidemia (Wu et al 2001;Ghayour-Mobarhan et al 2005, 2007; however, these clinically based studies also included patients with type 2 diabetes and established CVD, making detangling analysis open to imprecision. Indeed, anti-Hsp70 antibody levels are often reduced in patients with CVD, likely because of immunocomplex formation (Dulin et al 2010) and diabetic macrovascular/microvascular complications have been associated with lower anti-Hsp70 levels (Gruden et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although smoking (Newkirk et al 2012), hypercholesterolemia (Guisasola et al 2009), and microalbuminuria (Bianchi et al 2008) have been associated with increased circulating anti-Hsp70 levels and cases had greater prevalence/levels of these risk factors, the strength of the association was only slightly reduced by further adjustment for apoB, smoking, and AER. Previous studies have shown an association between circulating anti-Hsp70 antibody levels and single parameters of the MetS, such as hypertension, obesity, and dyslipidemia (Wu et al 2001;Ghayour-Mobarhan et al 2005, 2007; however, these clinically based studies also included patients with type 2 diabetes and established CVD, making detangling analysis open to imprecision. Indeed, anti-Hsp70 antibody levels are often reduced in patients with CVD, likely because of immunocomplex formation (Dulin et al 2010) and diabetic macrovascular/microvascular complications have been associated with lower anti-Hsp70 levels (Gruden et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular Hsp70 can also elicit an autoimmune response with the production of anti-Hsp70 antibodies and this has been implicated in atherosclerosis both in progression and severity in humans (Pockley et al 2003). Altered levels of circulating antibodies against Hsp70 have been associated with components of MetS, type 2 diabetes, and diabetic microvascular/ macrovascular complications (Wu et al 2001;GhayourMobarhan et al 2005GhayourMobarhan et al , 2007Gruden et al 2009). However, there are no data on circulating anti-Hsp70 levels in large series of patients with MetS prior to the development of CVD and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hsp70 protein and its antibody have been identified as being involved in the pathogenesis of hypertension, atherosclerosis, coronary heart disease, acute heat-induced illness and heat stroke (Gromadzka et al, 2001;Wu et al, 2001;Pockley et al, 2003;Jin et al, 2004). Hsp70.1 and Hsp70.2 are polymorphic, potentially accounting for variation in their functions and susceptibility to stress tolerance (Ross et al, 2003;Wu et al, 2004;Zhou et al, 2005).…”
Section: Hsp70 Genotype and Heat Stressmentioning
confidence: 99%
“…We subsequently observed that there was a significantly increased frequency of antibodies against Hsp70 (anti-Hsp70) in workers exposed to benzene, dust, heat, and noise, and that these stresses seemed to contribute to the production of an antibody against Hsp70. Interestingly, the presence of such antibodies was associated with benzene-poisoning, hypertension, noise-induced hearing loss, and abnormal changes of electrocardiography (Wu et al 1998(Wu et al , 2001bYang et al 2004b;Yuan et al 2005). Equally interesting was the observation that antibodies against Hsp70 occurred in higher titers in individuals who were more susceptible to heat-induced illness (Wang et al 2001;Wu et al 2001a).…”
Section: Association Of Anti-hsps With Environmental Stressesmentioning
confidence: 99%